INVESTIGATING FACTORS INFLUENCING EFL STUDENTS’ CRITICAL THINGKING SKILL AND READING ACHIVENTS IN READING CLASSROOM - Terasne, Terasne; Hanan, Ahmad; Utama, I Made Pemadi (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to investigate the factors that influence EFL students' critical thinking skills and reading achievement in reading classroom. To achieve the research objectives, so that the design of this research was a case study by taking 30 students at third semesters who program critical reading in English Study Program at the Faculty of Culture, Management and Business, Mandalika University of Education. The students were given critical thinking skill test in the form of reading an article and questionnaires consists of 22 items involves two dimensions including: psychology factors and cognitive factors influencing students’ critical thinking and reading achievement. Responses were collected and analyzed. Based on results of the study, it concludes that the students’ critical thinking skill in the scale of very poor. The result shows that critical thinking skill is not due to this individual's even though the individual was born with a state of vision and hearing problems that affect the innate ability critical thinking, the role of motivation and interest was also influencing the students’ critical thinking And Cognitive factors including memory, attention and awareness, and forgetting, influencing critical thinking and reading achievement in reading classroom.